The IMO compendium a collection of problems suggested for the International Mathematical Olympiads,1959-2009 - Djukic, Dusan; Jankovic, Vladimir; Matic, Ivan.; Petrovic, Nikola; SpringerLink (Online service). (New York, NY Springer New York, 2011)
The IMO Compendium is the ultimate collection of challenging high school level mathematics problems. It is an invaluable resource, not only for students preparing for competitions, but for anyone who loves and appreciates math. Training for mathematical olympiads is enjoyed by talented students throughout the world. Olympiads have become one of the primary ways to recognize and develop talented youth with a potential to excel in areas that require abstract thinking. Although the problems appearing at IMO do not involve advanced mathematics, they must be difficult and their solutions must arise from creative and clever insights rather than tedious calculations. In preparation for the distinguished International Mathematical Olympiad (IMO) competition, each participating country selects the top six high school students every year through a series of national olympiads. These students are invited to participate in the IMO, usually held in July. The IMO is a two-day contest where each day competitors are given three problems which they work on independently. The IMO host country appoints a special committee to which each country submits up to six problems. From this composite ?longlist? of problems, a ?shortlist? of 25-30 problems is created. The jury, consisting of one professor from each country, makes the final selection from the shortlist a few days before the IMO begins. The IMO has sparked a burst of creativity among enthusiasts to create new and interesting mathematics problems. It can be safely said that the IMO and shortlisted problems are among the well-crafted problems created in a given year. This book attempts to gather all of these problems with their solutions. In addition, the book contains all the available longlist problems, for a total of more than 2000 problems. - Publisher's description.
Electronic reproduction.
Keywords: Mathematics -- Problems, exercises, etc; Mathematics -- Competitions; Electronic books